Quality assurance in higher education in the Maldives: past, present and future - Shahuneeza Naseer, Mariyam; Al-Hidabi, Dawood Abdulmalek Yahya (2018)
Quality assurance in higher education is a hot topic with the increased number of students graduating from postgraduate programs offered by the higher education institutions. This qualitative study aimed to look at the history and the current status of the quality assurance mechanisms in the Maldives; identify its strengths and weaknesses; and make data informed recommendations. Critical event narrative inquiry was used and data were collected through interviews and analysis of documents. Content analysis of data collected revealed that Maldives was one of the very first countries in the region to establish such a mechanism and it was very similar to that of Australia. The most significant finding was that the body mandated to assure higher education quality did not have any power or regulatory authority. Therefore, it is important that the authority be an independent body established by an act of parliament with the regulatory power.